CASH CONTROL SYSTEM IN COMMUNISTIC CHINA. - Smith, Stephen Thomas (The Accounting Review, 1955)
Jinminpi (the "People's Money") is the currency now circulated in communistic China. It is usually abbreviated as JMP$. Only the People's Bank of China issues the notes. They are inconvertible paper money, and neither gold nor foreign exchange has been provided as reserves. Chinese communists generally follow Soviet communists. There is no exception in accounting. The cash control system in Communistic China is practically an extension of that in the Soviet Union. Simply speaking, there are three parts in the Soviet Ruble Control System: cash control; credit control; and transfer control. The democratic cash control differs from the Soviet cash control, not only in the operation but also in the object. The chief purpose of the democratic cash control is to insulate the abnormal fluctuation of cash circulated in foreign countries in order to stabilize the external value of the currency in foreign exchange market. By the cash control system; the central bank effectively controls the receipts and disbursements of all organizations. Since the cash in hand and cash settlements are limited, the volume and speed of money in circulation can be reduced and controlled by the central bank. Prices can, therefore, be stabilized.